Preventing child maltreatment: community approaches - Dodge, Kenneth A.; Coleman, Doriane Lambelet (Duke series in child development and public policy, 2009)
The history of science and child abuse prevention : a reciprocal relationship / Deborah Daro -- Preventing child abuse and neglect with home visiting by nurses / David L. Olds ... [et al.] -- Toward a population-based paradigm for parenting intervention, prevention of child maltreatment, and promotion of child well-being / Ronald J. Prinz -- Community-level prevention of child maltreatment : the Durham family initiative / Kenneth A. Dodge ... [et al.] -- How strong communities restored my faith in humanity : children can live in safety / Gary B. Melton -- The period of purple crying : keeping babies safe in North Carolina / Desmond Runyan & Adam Zolotor -- Quality improvement in child abuse prevention programs / Robert T. Ammerman ... [et al.] -- Differential response / Jane Waldfogel -- Innovations in child maltreatment prevention : resolving the tension between effective assistance and violations of privacy / Doriane Lambelet Coleman -- Healing in the place of last resort : the role of the dependency court within community-based efforts to prevent child maltreatment / Cindy S. Lederman -- Preventing maltreatment or promoting positive development where should a community focus its resources? : a policy perspective / Michael S. Wald